Analisis Kesalahan Berbahasa Bidang Morfologi Pada Teks Karangan Narasi Siswa Kelas V SD Negeri 5 Dersalam - Vebby Meilia Roja; Sunaisah Sunaisah; Iffatul Ulya Rosyadi; Rani Setiawaty (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
This study aims to examine errors in the morphological aspects found in the narrative texts of fifth-grade students at SD Negeri 5 Dersalam. The methodology employed is qualitative descriptive, focusing on data containing morphological errors or improper sentence usage. The narrative compositions of the fifth-grade students from SD Negeri 5 Dersalam serve as the primary data source. Data collection was conducted through the documentation of student compositions. The data analysis was carried out using the Milles Huberman analysis model. The research findings indicate a variety of language errors in the students' narrative texts, including errors in the use of prepositions, incorrect writing of standard words, and errors in affixation writing .